Counterions between charged polymers exhibit liquid-like organization and dynamics. - Angelini, T; Golestanian, R; Coridan, R; Butler, J; Beraud, A; Krisch, M; Sinn, H; Schweizer, K; Wong, G (2006)
Current understanding of electrostatics in water is based on mean-field theories like the Poisson-Boltzmann formalism and its approximations, which are routinely used in colloid science and computational biology. This approach, however, breaks down for highly charged systems, which exhibit counterintuitive phenomena such as overcharging and like-charge attraction. Models of counterion correlations have been proposed as possible explanations, but no experimental comparisons are available. Here, collective dynamics of counterions that mediate like-charge attraction between F-actin filaments have been directly observed in aqueous solution using high-resolution inelastic x-ray scattering down to molecular length-scales. We find a previously undescribed acoustic-like phonon mode associated with correlated counterions. The excitation spectra at high wave-vector Q reveal unexpected dynamics due to ions interacting with their "cages" of nearest neighbors. We examine this behavior in the context of intrinsic charge density variations on F-actin. The measured speed of sound and collective relaxation rates in this liquid agree surprisingly well with simple model calculations.